Maximum entropy model-based spatial sinkhole occurrence prediction in Karapınar, Turkey - Fatih Sarı; Mustafa YALÇIN (Kuwait Journal of Science)
Sinkholes in Karapınar and their rapidly increasing occurrence rate are considered one of the main hazards that threaten arable lands and human life. The sudden occurrence and unavoidable characteristics of sinkholes make them more dangerous and challenging to avoid. More than 300 sinkholes have been recorded in the Karapınar region of Konya province in Turkey. There are intensive agricultural activities in the region, and therefore over 60,000 water wells are used to meet the demand. Thus, drought, the effects of climate change and decreasing precipitation rate reveal stress on sinkhole occurrence due to the geological structure of the region and its high tendency to sinkholes since ancient times due to its volcanic history.